Dietary synbiotics improved the growth, feed utilization and intestinal structure of largemouth bass (Micropterus salmoides) juvenile. (26th November 2019) - Yang, Pinxian; Yang, Weining; He, Ming; Li, Xiaoqin; Leng, Xiang‐Jun
Abstract: This study investigated the effect of dietary synbiotics on the growth, feed utilization and intestinal histology of largemouth bass ( Micropterus salmoides ). A commercial synbiotic product containing dried powder of yeast, Bacillus subtilis and mannan oligosaccharides was supplemented in basal diet with 0 g/kg (control), 1.0, 2.0, 4.0 and 6.0 g/kg, respectively, and then, the five diets were fed to largemouth bass with body weight of 4.5 ± 0.1 g for 8 weeks. The results showed that the supplementation of 2.0, 4.0 and 6.0 g/kg synbiotics increased weight gain by 20.6%, 17.7% and 11.8% ( p < .05) and decreased feed conversion ratio by 0.20, 0.18 and 0.12 ( p < .05), respectively, when compared to the control. The protein retention, lipid retention, apparent digestibility coefficient of dry matter and crude protein, and the intestinal villus height and width of 2.0 and 4.0 g/kg synbiotic groups were significantly higher than those of the control ( p < .05). The intestinal protease activity and serum lysozyme activity were increased by the addition of 2.0 and 4.0 g/kg synbiotics ( p < .05). In conclusion, dietary synbiotics improved the growth, feed utilization and intestinal structure of juvenile largemouth bass, and the recommended inclusion level was 2.0–4.0 g/kg.